Spatiotemporal responsive hydrogel microspheres for the treatment of gastric cancer - Wang, Li; Fan, Lu; Filppula, Anne M.; Wang, Yu; Shang, Luoran; Zhang, Hongbo (John Wiley and Sons Inc, 2025)
The development of tumor drug microcarriers has attracted considerable interest due to their distinctive therapeutic performances. Current attempts tend to elaborate on the micro/nano-structure design of the microcarriers to achieve multiple drug delivery and spatiotemporal responsive features. Here, the desired hydrogel microspheres are presented with spatiotemporal responsiveness for the treatment of gastric cancer. The microspheres are generated based on inverse opals, their skeleton is fabricated by biofriendly hyaluronic acid methacrylate (HAMA) and gelatin methacrylate (GelMA), and is then filled with a phase-changing hydrogel composed of fish gelatin and agarose. Besides, the incorporated black phosphorus quantum dots (BPQDs) within the filling hydrogel endow the microspheres with outstanding photothermal responsiveness. Two antitumor drugs, sorafenib (SOR) and doxorubicin (DOX), are loaded in the skeleton and filling hydrogel, respectively. It is found that the drugs show different release profiles upon near-infrared (NIR) irradiation, which exerts distinct performances in a controlled manner. Through both in vitro and in vivo experiments, it is demonstrated that such microspheres can significantly reduce tumor cell viability and enhance the efficiency in treating gastric cancer, indicating a promising stratagem in the field of drug delivery and tumor therapy. © 2024 The Author(s). Aggregate published by SCUT, AIEI, and John Wiley & Sons Australia, Ltd.